Novel activated Ni-P-hBN composite powder for efficient solid lubricant coating application - Maleque, Md. Abdul (2015)
As new technologies evolve, new demands are created for protective coatings which are required to have stability over a range of quite aggressive service conditions. For instance, the surfaces of shafts, bearings and steam turbine blades for use in turbine engines are to be protected against daunting effect of high-temperature dry sliding wear. Under this condition, conventional liquid lubrication is inadequate due to the limitation on the temperature at which the liquid lubricant can be used; moreover, most of the materials for unlubricated hard coatings such as TiC ceramics are not suitable for dry sliding applications due to their high friction coefficient and wear rate. In order to meet the requirement of extreme and demanding tribological applications, high- performance wear resistant composite coating with outstanding self-lubricating properties have been developed in this new innovation based on the advanced lubrication concept of combining hard TiC and soft reinforcement phase of hexagonal boron nitride (hBN). hBN is a well known effective solid lubricant for high-temperature application. Due to the challenge of its non-wettability with most metal-ceramic matrices, a novel electroless plating technique was developed by the innovators to coat the surface of hBN with thin layer of Nickel-Phosphorous (Ni-P) deposits which has been patented recently. Finally, a cheaper powder preplacement and tungsten inert gas (TIG) arc torch method was employed to consolidate the newly developed composite hBN powder particles in the near-surface region of AISI 4340 low alloy steel (LAS). Laboratory tests were carried out to assess the tribological performance of the developed TiC/Ni-P-hBN hybrid composite coated steel as compared to TiC and TiC/hBN coatings. The tribological assessments of the new composite coated steel product exhibitted an improved performance in term of microstructural integrity or morphology and stable frictional control at high temperature.